2002
DOI: 10.1016/s1044-0305(02)00372-0
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent H/D exchange of compact and elongated cytochrome c ions in the gas phase

Abstract: Isotopic exchange reactions of compact and elongated conformations of gaseous cytochrome c ions (ϩ5 and ϩ9 states) with D 2 O have been measured as a function of temperature (from 300 to ϳ440 K) using ion mobility techniques. Rate constants for those sites that exchange at high temperatures (Ͼ400 K) are about an order of magnitude smaller than rate constants for sites that exchange at 300 K. Although the exchange rates decrease, the maximum exchange levels for rapidly exchanging sites increase with temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
113
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(116 citation statements)
references
References 76 publications
3
113
0
Order By: Relevance
“…The pressures of deuterating reagent in linear trap experiments can be ϳ5 ϫ 10 Ϫ3 Torr, ca. 10 3 times greater than used in 3D traps [20], 10 1 to 10 2 times greater than used in mobility experiments [26,27], and 10 3 to 10 4 times greater than in ICR experiments [21][22][23][24][25]. The higher pressures allow faster exchange experiments.…”
mentioning
confidence: 96%
“…The pressures of deuterating reagent in linear trap experiments can be ϳ5 ϫ 10 Ϫ3 Torr, ca. 10 3 times greater than used in 3D traps [20], 10 1 to 10 2 times greater than used in mobility experiments [26,27], and 10 3 to 10 4 times greater than in ICR experiments [21][22][23][24][25]. The higher pressures allow faster exchange experiments.…”
mentioning
confidence: 96%
“…Three exchanges are observed for arginine and argininecontaining tri-peptide [M ϩ H] [15]. Valentine and Clemmer used ion mobility-mass spectrometry to examine the conformation dependence of H/D exchange reactions, and suggested that ion conformation has a significant effect on H/D exchange [16,17].Compared with the intensive investigations carried out on the conformational characterization of peptides and proteins using solution-phase H/D exchange reaction chemistry, the corresponding gas-phase studies are much less comprehensive. The key question regarding gas-phase H/D exchange is: does the "solvent molecule," i.e., H/D exchange reagent, sample the entire "available surface area" of the peptide/protein ion, or is H/D exchange limited by other factors?…”
mentioning
confidence: 99%
“…Three exchanges are observed for arginine and argininecontaining tri-peptide [M ϩ H] [15]. Valentine and Clemmer used ion mobility-mass spectrometry to examine the conformation dependence of H/D exchange reactions, and suggested that ion conformation has a significant effect on H/D exchange [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Higher-order structural features of peptides have been known to affect collision-induced dissociation spectra and influence sequence assignments and fragmentation mechanisms [21][22][23][24]. While many studies have investigated the gas-phase conformations of peptides [25][26][27][28][29][30][31][32] and proteins [33][34][35], very few have focused on oligonucleotides [36].…”
mentioning
confidence: 99%